Analisis Fiqh Kontemporer tentang Nikah Beda Agama dan Relevansinya dengan Moderasi Beragama - Muhammad Syar’i Ramadhoni; Ahmad Rifki; Helmi (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The issue of Interfaith Marriage presents a complex discourse in Islamic law, creating tension between nash (sacred texts) and contemporary social realities. This research aims to analyze the perspective of Contemporary Fiqh regarding the law on Interfaith Marriage and identify its relevance to the Religious Moderation agenda in Indonesia. Employing a qualitative research method with normative-juridical and comparative approaches, this article examines legal texts (fiqh) and concepts of socio-religious ethics. The analysis shows that the majority of Contemporary Fiqh establishes an absolute prohibition (haram). This prohibition is strongly based on the principle of sadd az zari'ah, which means 'blocking the means to evil,' aligning with the ushul fiqh rule: (Preventing harm takes precedence over attaining benefit), in order to safeguard faith (hifz ad-din) and progeny (hifz an-nasl). This ruling is further supported by the Quranic prohibition (Q.S. Al-Baqarah: 221) and Indonesian positive law regulations, specifically Article 40 letter (c) and Article 44 of the Compilation of Islamic Law (KHI). Meanwhile, Religious Moderation serves as a manhaj as-shifat (methodology of attitude) that demands the implementation of tawassuth (balanced) and i'tidal (just) principles in addressing social realities. In conclusion, the relevance of Religious Moderation lies in ensuring that these fiqh differences are not implemented fanatically (ghuluw) but are managed proportionally to foster social harmony (tasāmuh) in Indonesia.